PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK MENENTUKAN PERANGKINGAN GURU BERPRESTASI STUDI KASUS: SDN RAMBUTAN 03 PAGI - Rosi Kusuma Serli (Jurnal Informatika Upgris, 2022)
This study contains the implementation of the Simple Additive Weighting (SAW) method to determine the ranking of excellent teachers in Rambutan 03 Pagi Elementry School. The finding and determining of ranking the excellent teachers are the main problem conducted in this research, specifying the ranking of teachers aims to classify and identify that the teachers are appropriate to the criteria determined. In the problem and purpose of determining the ranking of the excellent teachers, the method used is to calculate the data manually by using Microsoft Excel and calculate the formula of the Simple Additive Weighting (SAW) method. By using this method, calculations are performed to produce teachers’ data starting from the first rank to the end. From the calculations performed using the Simple Additive Weighting (SAW) method, the calculation data of excellent teachers starts from rank 1 to 17. 92,5 is the highest value result and 33,83 is the lowest value result in determining the excellent teachers at Rambutan 03 Pagi Elementary School. The difference in the assessment’s result can be seen in the result of the ranking process.